PENGEMBANGAN KEWIRAUSAHAAN (ENTREPRENEURSHIP) OLAHAN IKAN MAS DAN BRANDING PRODUCT GUNA MENINGKATKAN KESEJAHTERAAN MASYARAKAT DI DESA PEKURUN KECAMATAN ABUNG PEKURUN, KABUPATEN LAMPUNG UTARA - Rosy Febriani Daud,; Ade Rama Dani Kusuma,; Alfahri Sobriyan Nur Huda, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
Fish is an aquatic resource that contains many benefits because it is a good source of protein for the body. In addition, fish also contains various substances that are very beneficial for the body. Fish is also a local commodity that is widely used as a source of livelihood with a fairly high level of production. However, due to the lack of knowledge of fish farmers in processing fishery products, production and public interest are not comparable. The purpose of this program is so that fish farmers can take full advantage of fishery products, considering that carp is a fish that is most susceptible to temperature changes and causes death and extends the shelf life of meat. Therefore, we provide an alternative by processing fish into shreds. The specific target to be achieved with this program is to train caged fish farmers to be more skilled. It is hoped that after this training, the community can become entrepreneurs in processing fishery products to be more innovative and varied, such as Abon Ikan Mas with direct assistance and monitoring to fish farmers. The method used is socialization, training and mentoring. The expected outcome is that the Pekurun village community, Abung Pekurun District, North Lampung Regency can be more independent and have skills in processing carp meat and bones to be produced in order to improve the welfare of the village community.